Constructing Histories : Archaic Freshwater Shell Mounds and Social Landscapes of the St. Johns River, Florida - Randall, Asa R. (Book collections on Project MUSE., 2015)
This book provides a challenging interpretation of ancient hunter-gatherer societies along the St. Johns River in northeast Florida and reveals that these mounds were not just garbage dumps, but rather intentionally constructed sacred mounds of immense significance to their creators. The book presents a new theoretical framework for investigating shell mounds as places of history-making through daily living, ceremonies, and burial ritual.